Optimisation of The Cathodic Stripping Voltammetry For The Determination of Metal Ni(II) in The River Water - pardi, Hilfi; Fitriyah, Dina (Al-Kimia, 2023)
The study was carried out to determination the metal Ni(II) in river water samples using cathodic stripping voltammetry (CSV) method. In order to achieve optimum conditions for the determination of metal Ni(II), the accumulation potential and accumulation time conditions of the CSV method have been achieved. The results of this research obtained under the optimum conditions for Ni(II) measurement using an electrolyte solution of ammonium chloride with a potential accumulation (accv) of -0.7 V and a time accumulation (acct) of 60 s. The relative standard deviation of the 10 µg/L Ni(II) standard solution (n=8) is 0.53%, the recovery value is 98.82%. The CSV method for the determination of Ni(II) metal has been successfully applied to river water samples.